Kebebasan Ekonomi Vis a Vis Intervensi Negara: Perspektif Ibn Khaldun - Agus Fakhrina (Jurnal Penelitian, 2017)
This research was aimed to explore the economic freedom vis a vis government intervention according to Ibn Khaldun. To answer this question, researcher studied al-Muqaddimah of Ibn Khaldun. The ideas of Ibn Khaldun in his al-Muqaddimah were analized by using content analysis. Beside that, I also used Karl Mannheim’s sociology of knowledge approach to analyze his ideas. The result revealed that Ibn Khaldun emphasized the economic activities had to be free from the restrictive power of the government. The economic freedom, however, had not to be free from rule of game. It had to be under the control of the rule of game, and to do that the role of government was very necessary. Based on Karl Mannheim’s sociology of knowledge, Ibn Khaldun ideas were influenced by social knowledge determination in his life and he also used his perspective as Moslem to explore his ideas. It could be said that there was so strong relation between Ibn Khaldun ideas and the social reality in his life. Thus, his knowledge type was ideological, not utopian.